The Impact of Cholesterol, DHA, and Sphingolipids on Alzheimer's Disease. (19th February 2014) - Grimm, Marcus O. W.; Zimmer, Valerie C.; Lehmann, Johannes; Grimm, Heike S.; Hartmann, Tobias
Abstract : Alzheimer's disease (AD) is a devastating neurodegenerative disorder currently affecting over 35 million people worldwide. Pathological hallmarks of AD are massive amyloidosis, extracellular senile plaques, and intracellular neurofibrillary tangles accompanied by an excessive loss of synapses. Major constituents of senile plaques are 40–42 amino acid long peptides termed β -amyloid (A β ). A β is produced by sequential proteolytic processing of the amyloid precursor protein (APP). APP processing and A β production have been one of the central scopes in AD research in the past. In the last years, lipids and lipid-related issues are more frequently discussed to contribute to the AD pathogenesis. This review summarizes lipid alterations found in AD postmortem brains, AD transgenic mouse models, and the current understanding of how lipids influence the molecular mechanisms leading to AD and A β generation, focusing especially on cholesterol, docosahexaenoic acid (DHA), and sphingolipids/glycosphingolipids.